2020
DOI: 10.1093/ehjci/jeaa106
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive development of concomitant secondary mitral and tricuspid regurgitation after transcatheter aortic valve replacement

Abstract: Aims Concomitant secondary atrioventricular regurgitation is frequent in patients with severe aortic stenosis scheduled for transcatheter aortic valve replacement (TAVR). The future implications of leaving associated valve lesions untreated after TAVR remain unknown. Aim of the present study was to characterize the evolution of concomitant secondary atrioventricular regurgitations and to evaluate their impact on long-term prognosis. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
1
13
0
2
Order By: Relevance
“…In patients with severe AS, TR is, at least in part, a consequence of increased afterload due to AS (21). Thus, clinically relevant TR has been shown to improve in 15% to 60% of patients undergoing TAVR (4,5,9,10,22). In contrast, owing to the dynamic and load dependent nature of TR, progression of TR after TAVR has been reported in 4%-11% of patients with nonsignificant TR at baseline (4,5,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with severe AS, TR is, at least in part, a consequence of increased afterload due to AS (21). Thus, clinically relevant TR has been shown to improve in 15% to 60% of patients undergoing TAVR (4,5,9,10,22). In contrast, owing to the dynamic and load dependent nature of TR, progression of TR after TAVR has been reported in 4%-11% of patients with nonsignificant TR at baseline (4,5,23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, owing to the dynamic and load dependent nature of TR, progression of TR after TAVR has been reported in 4%-11% of patients with nonsignificant TR at baseline (4,5,23). Previous studies suggested that persistent or worsening of moderate or greater TR was associated with an increased risk of mortality (6,9,10,22,23). Consistent with these studies, more than half of patients with significant baseline TR had an improvement of at least one grade after TAVR, while a small proportion of patients (5% to 7%) with baseline <massive TR had a progression in the TR severity after TAVR in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of atrioventricular valve regurgitation was higher among LFLG compared to HG patients, as expected. This is relevant because persistent MR or TR after TAVI is associated with a two-fold mortality increase, as recently reported by Winter et al [ 19 ]. To what extent this is applicable particularly to LFLG patients remains to be elucidated.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, many other variables can predict improvement in secondary or mixed MR: dilated LV and a decreased ejection fraction (indicating a greater propensity for reverse remodeling), LV dyssynchrony due to new left bundle branch block, right ventricular pacing or ischemic wall motion abnormalities, and a significant decrease in the transaortic pressure gradient (including a high preoperative transvalvular pressure gradient) [59]. Moreover, secondary atrioventricular MR is common in patients with severe AS undergoing AVR [60]. Therefore, it is not surprising that the occurrence of atrial fibrillation, pulmonary hypertension, and atrial and/or mitral annulus dilatation, both of which are associated with higher chronic MR repercussions, has been linked to more limited improvement in MR [13].…”
Section: The Effects Of Valve Replacement For Aortic Stenosis On Mitral Regurgitationmentioning
confidence: 99%